2017
DOI: 10.1590/1807-3107bor-2017.vol31.0010
|View full text |Cite
|
Sign up to set email alerts
|

Association between the clinical severity of oral lichen planus and anti-TPO level in thyroid patients

Abstract: This study considered a possible relationship between the severity of oral lichen planus (OLP), serum anti-TPO autoantibodies (TPOAb) titer and thyroid disease in OLP patients. Forty-six OLP patients with positive TPOAb results (> 35 IU/ml) who had also been diagnosed with thyroid disease were included in the study group. The control group consisted of 46OLP patients with no thyroid disease. The study and control groups (92) were divided to two subgroups of erosive OLP (EOLP) and non-erosive OLP (NEOLP). Serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 29 publications
0
13
0
1
Order By: Relevance
“…OLP has recently been associated with LT 4 intake (Robledo‐Sierra et al., , ) and hypothyroidism (Garcia‐Pola et al., ; Lo Muzio et al., ; Robledo‐Sierra et al., ; Siponen et al., ). To the best of our knowledge, only three studies have investigated the serum levels of antithyroid antibodies in patients with OLP (Alikhani et al., ; Chang et al., ; Lin et al., ). Chang et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…OLP has recently been associated with LT 4 intake (Robledo‐Sierra et al., , ) and hypothyroidism (Garcia‐Pola et al., ; Lo Muzio et al., ; Robledo‐Sierra et al., ; Siponen et al., ). To the best of our knowledge, only three studies have investigated the serum levels of antithyroid antibodies in patients with OLP (Alikhani et al., ; Chang et al., ; Lin et al., ). Chang et al.…”
Section: Discussionmentioning
confidence: 99%
“…This treatment also alleviated the symptoms and reduced the size and severity of ulceration in existing OLP lesions. Finally, a study conducted in 96 Iranian patients with OLP showed that the serum levels of TPOAb were significantly associated with an increased risk of erosive OLP (OR = 4.02, 95% CI 1.21–13.4; p = .023) (Alikhani et al., ). These results suggest that some immunological mechanism in Hashimoto's thyroiditis involving antithyroid antibodies may also play an important pathogenic role in a subgroup of patients with OLP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the precise mechanisms for autoantibody induction and production in the sera of OLP patients are unknown, AITD may lead to the production of antigens in the damaged thyroid tissue, which then activate antigen-specific B cells to produce antibodies locally and in the blood circulation of OLP patients. The severity of OLP lesions is directly linked to TPOAb levels [23]. In addition, circulating thyroid antibodies in HT patients contribute to the triggering of oral mucosa-specific autoimmune responses, leading to OLP [11].…”
Section: Potential Mechanisms Underlying Thementioning
confidence: 99%
“…In 2016, a study was conducted by Chinese Society of Endocrinology, revealing that more than 40% of the population suffered from TD (8). In the study of the relationship between OLP and TD, some scholars found that erosive OLP has been associated with anti-TPO autoantibodies (TPOAb) in thyroid patients, it may be useful to determine TPOAb levels of such patients to diagnose a possible undetected thyroid disorders and followup for malignancy (9). HT is a kind of TD with incidence from 0.4 to 2% in the general population (10).…”
Section: Introductionmentioning
confidence: 99%